The problems facing Obama - Schiffrin, André (Sens public)

(untitled) (Département des littératures de langue française, 2009)
As everyone knows by now, the election of Obama was greeted with great joy and relief in the United States-and elsewhere. The racist and reactionary campaign that McCain, surprisingly, decided to run did not have the effect he hoped for. Until then, a moderate and decent man, McCain was persuaded that he could only win by using and condoning extremist attacks. Symbolic of this turn was the choice of Sarah Palin, who played on all the traditional right wing fears and added many more, dividing the country into the real America, that would back her and the others, urban, elitist, intellectual and of course black, who would not.